The relationship between multimorbidity, obesity and functional impairment in older adults. Issue 5 (3rd February 2022) - Lynch, David H.; Petersen, Curtis L.; Fanous, Marco M.; Spangler, Hillary B.; Kahkoska, Anna R.; Jimenez, Daniel; Batsis, John A.
Abstract: Background: Declining mortality rates and an aging population have contributed to increasing rates of multimorbidity (MM) in the United States. MM is strongly associated with a decline in physical function. Obesity is an important risk factor for the development of MM, and its prevalence continues to rise. Our study aimed to evaluate the associations between obesity, MM, and rates of functional limitations in older adults. Methods: We analyzed body mass index (BMI) and self‐reported comorbidity data from 7261 individuals aged ≥60 years from the National Health and Nutrition Examination Surveys 2005–2014. Weight status was defined based on standard BMI categories. MM was defined as 2 or more comorbidities, while functional limitations were self‐reported. Adjusted logistic regression quantified the association between standard BMI categories and MM. We also examined the difference in the prevalence of limitations between those with and without MM. Results: The overall proportion of individuals with concomitant MM and obesity was 27.0%. Compared to a normal BMI, older adults with obesity had higher odds of MM (Prevalence odds ratio 1.79, 95% CI 1.49, 2.12). Overall, 67.5% of patients with MM also reported a functional limitation, with rates of functional limitation increasing with increasing BMI. When evaluating functional limitations in those with MM by BMI class, 90% of patients classified as severely obese (BMI ≥40 kg/m 2 ) with MM also had a concomitant functional limitation. Conclusions: Compared to normal weight status, obesity is associated with an increased burden of MM and functional limitation among older adults. Our results underscore the importance of identifying and addressing obesity, MM, and functional limitation patterns and the need for evidence‐based interventions that address all three conditions in this population.